Calculation of Oil Recoverable Reserves on the Basis of Dynamic Models (in the example of Gunashli field Pereriv formation) - Suleimanova, V.M.; Jabizade, N.I. (Herald of Azerbaijan Engineering Academy, 2023)
The annual oil production of the Pereriva formation, analyzed in the article, is more than 1.7 million tons. The final coefficient is 0.6, and the current coefficient value is 0.55. To continue the effective development of this formation with the high production rates, an analysis based on geological and mathematical models is considered relevant. The Evolutionary Modeling program (Gompertz-Makem curves) was used to forecast the field production. These curves project production and initial recoverable reserves 10 years into the future.